2015
DOI: 10.13075/ijomeh.1896.00417
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of biomarkers as intermediate endpoints in health risks posed by occupational lead exposure

Abstract: The article concerns potential harmful effects of exposure to lead. Although the occurrence of severe lead poisoning has receded in several countries, occupational exposure resulting in moderate and clinically symptomatic toxicity is still common. An earlier and precise characterization of an individual response is obligatory in order to assess the possible risks for human health. Biomarkers may fill important gaps in the path from exposure to a disease. Specifically speaking, emerging (DNA double strand break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
(76 reference statements)
0
6
0
1
Order By: Relevance
“…Urinary kidney biomarkers such as NAG, β 2-MG, α 1-MG are commonly regarded as indexes of renal tubular injury, and are always used as diagnostic parameters in renal injury elicited by heavy metals14. The average blood lead level in the lead-exposed subjects in the current study was 121  μ g/L, which is far lower than the diagnostic criteria of lead poisoning, suggestive of an early and subclinical stage of lead poisoning.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Urinary kidney biomarkers such as NAG, β 2-MG, α 1-MG are commonly regarded as indexes of renal tubular injury, and are always used as diagnostic parameters in renal injury elicited by heavy metals14. The average blood lead level in the lead-exposed subjects in the current study was 121  μ g/L, which is far lower than the diagnostic criteria of lead poisoning, suggestive of an early and subclinical stage of lead poisoning.…”
Section: Discussionmentioning
confidence: 61%
“…As one of the most easily accumulated poisonous substances in human body, lead exposure is closely related to chronic renal injury10111920. Early diagnosis of lead-induced kidney damage still lacks appropriate methods with great accuracy and precision, but is critical for long term prognosis in workers with occupational lead exposure142122. The current study examined healthy workers with occupational lead exposure and compared the traditional urinary biomarkers with KIM-1 to evaluate their ability in predicting the lead-induced renal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ołów jest wykorzystywany w produkcji i recyklingu akumulatorów, naprawie samochodów, produkcji tworzyw sztucznych, ceramiki, farb i barwników. Odgrywa rów-nież istotną rolę w produkcji i recyklingu baterii [5].…”
Section: Wyniki Przegląduunclassified
“…The most common routes of lead exposure are respiratory and digestive tracts, through which lead develops toxic effects on every organ and system of the body [ 4 ]. In recent years, it has been well demonstrated that lead or its compounds shows potential genotoxicity to various research subjects under different conditions [ 5 10 ], but few studies have explored lead-induced genotoxicity in human cells. TK6 human lymphoblasts with good differentiation ability, stable genome, and normal expression of P53, are widely used in genotoxicity studies [ 11 14 ] and can be useful for the in vitro study of human genotoxicity.…”
Section: Introductionmentioning
confidence: 99%